2020
DOI: 10.1186/s13059-020-02020-4
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and the presence of helminths is associated with gut microbiome composition in Cameroonians

Abstract: Background African populations provide a unique opportunity to interrogate host-microbe co-evolution and its impact on adaptive phenotypes due to their genomic, phenotypic, and cultural diversity. We integrate gut microbiome 16S rRNA amplicon and shotgun metagenomic sequence data with quantification of pathogen burden and measures of immune parameters for 575 ethnically diverse Africans from Cameroon. Subjects followed pastoralist, agropastoralist, and hunter-gatherer lifestyles and were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 108 publications
3
75
1
Order By: Relevance
“…In this study we characterize the gut microbiome in a pediatric population of ethnically diverse Cameroonian children with and without HIV. Children living in Cameroon and in SSA broadly have been underrepresented in studies of the gut microbiome, with studies conducted in SSA often focusing on populations with specific lifestyles such as agrarian, pastoralist, or hunter-gathers 4 , 19 26 . However, one study conducted in individuals in three populations along an urbanization gradient in Cameroon indicated that urban individuals have retained most of their gut eukaryotic and bacterial diversity despite significant changes in diet compared to the rural areas 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we characterize the gut microbiome in a pediatric population of ethnically diverse Cameroonian children with and without HIV. Children living in Cameroon and in SSA broadly have been underrepresented in studies of the gut microbiome, with studies conducted in SSA often focusing on populations with specific lifestyles such as agrarian, pastoralist, or hunter-gathers 4 , 19 26 . However, one study conducted in individuals in three populations along an urbanization gradient in Cameroon indicated that urban individuals have retained most of their gut eukaryotic and bacterial diversity despite significant changes in diet compared to the rural areas 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In Cameroon, customary food staples vary across and within ethnic groups as the preferences for one staple over another are influenced by cultural history/identity and geography 28 . Though some research has investigated the link between subsistence lifestyle and microbiome composition in rural Cameroon 19 , much remains to be discovered about how the interplay between cultural identity, geography, and diet influences microbiome structure and function across Cameroon’s ~ 250 ethnic groups. Unfortunately, during the present study, diet data specific to each community was not collected, and thus constitute a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But not all STH studies support these findings [22], and their potential pathology has not been determined [16]. One study found that gut microbiome composition was predictive of an STH infection [23]. However, ascribing cause and effect from this finding is not simple, as gut microbial composition may influence susceptibility to STH infection [24].…”
Section: Introductionmentioning
confidence: 99%
“…Fecal microbiota transplants in Italian, US, Canadian, and Dutch populations have proved effective for the treatment of Clostridioides difficile infections (Ianiro et al, 2018;Jiang et al, 2017;Lee et al, 2016;van Nood et al, 2013). Moreover, an individual's gut microbiome composition can predict colonization by gut parasites like Entamoeba and soil-transmitted helminths in rural African populations (Morton et al, 2015;Rubel et al, 2020), and by Vibrio cholera in a pediatric Bangladeshi cohort (Midani et al, 2018). These seminal reports highlight the importance of exploring the causal relationship between the gut microbiome and enteric infections while considering global differences in microbiomes.…”
Section: Introductionmentioning
confidence: 99%